2022
DOI: 10.1093/immadv/ltac003
|View full text |Cite
|
Sign up to set email alerts
|

Engineering CAR-NK cells: how to tune innate killer cells for cancer immunotherapy

Abstract: Cell therapy is an innovative approach that permits numerous possibilities in the field of cancer treatment. CAR-T cells have been successfully used in hematologic relapsed/refractory patients. However, the need for autologous sources for T cells is still a major drawback. CAR-NK cells have emerged as a promising resource using allogeneic cells that could be established as an off-the-shelf treatment. NK cells can be obtained from various sources, such as peripheral blood (PB), bone marrow, umbilical cord blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 156 publications
0
6
0
Order By: Relevance
“…ADAM17 is also a member of the metalloproteinase family that may have a similar function. Recently it was found that ADAM17 has the ability to hydrolyze MICA/B on the surface of tumor cells to generate soluble MICA/B (sMICA/B) (52), the latter of which alters the conformation of NKG2D on the surface of NK cells (234) and affects the recognition and binding of membranous MICA with NKG2D, thereby inhibiting NK activation signals and reducing the killing sensitivity of NK cells to tumor cells (235). Knockdown of ADAM17 prohibits MICA shedding and boosts MICA expression on the surface of hepatocellular carcinoma cells (131).…”
Section: Regulation Of Nk Cells By Adam17mentioning
confidence: 99%
“…ADAM17 is also a member of the metalloproteinase family that may have a similar function. Recently it was found that ADAM17 has the ability to hydrolyze MICA/B on the surface of tumor cells to generate soluble MICA/B (sMICA/B) (52), the latter of which alters the conformation of NKG2D on the surface of NK cells (234) and affects the recognition and binding of membranous MICA with NKG2D, thereby inhibiting NK activation signals and reducing the killing sensitivity of NK cells to tumor cells (235). Knockdown of ADAM17 prohibits MICA shedding and boosts MICA expression on the surface of hepatocellular carcinoma cells (131).…”
Section: Regulation Of Nk Cells By Adam17mentioning
confidence: 99%
“…Specifically, NK cells can be obtained either from autologous or allogenic peripheral blood. Nevertheless, the limited amount of autologous or allogenic NK cells obtained from peripheral blood not only impedes NK cell expansion, but also possesses heterogenous issues and is sensitive to freeze-thaw cycles which eventually reduces the efficiency of transduction ( 29 ). Therefore, another approach such as using NK cell lines is preferred to overcome the disadvantages of primary NK cells from peripheral blood.…”
Section: Advancement Of Car-nk Cell Productionmentioning
confidence: 99%
“…showed that incorporation of activating receptors such as natural killer group 2 member D (NKG2D) in the transmembrane region of CAR structure and 2B4 as a co-stimulating domain was able to enhance the cytotoxicity of CAR-NK cells, thus demonstrating the highest efficacy to eradicate cancer cells compared to other CAR structures which did not use NKG2D ( 82 ). However, 2B4 cannot be used alone and should bind with CD3 for full CAR-NK cell activation ( 29 ). Parihar et al.…”
Section: Strategies To Tackle Challenges In Car-nk Cell Therapymentioning
confidence: 99%
“…Despite their promise for off-the-shelf therapy, there remain significant hurdles to implementing CAR-NK cells including technical challenges of efficient manufacturing, in-patient expansion and persistence, and optimizing their potency for maximum impact. 161 Because of their abundance in solid tumors and ability to infiltrate the TME, macrophages are another innate immune cell type highly sought after for engineering applications. Although broadly considered immunosuppressive in the TME context, macrophages can have potent antitumor capabilities and can be repolarized or activated in vivo with anti-CD47 or CD40 agonist for antitumor functions.…”
Section: Engineering Alternative Cell Types For Multilineage Therapymentioning
confidence: 99%
“…More recent studies focusing on solid tumors have demonstrated preclinically efficacy, 160 and there are now multiple phase I clinical trials assessing CAR‐NK cells in solid tumors; however, these have yet to report efficacy results. Despite their promise for off‐the‐shelf therapy, there remain significant hurdles to implementing CAR‐NK cells including technical challenges of efficient manufacturing, in‐patient expansion and persistence, and optimizing their potency for maximum impact 161 …”
Section: Principle 5: Designing Multi‐nodal Approaches For Tumor Erad...mentioning
confidence: 99%